Evaluation of mir-377-3p Expression in Patients with Multiple Sclerosis - Majid Amini Khorasgani; Parisa Mohammady Nejad; Mohammad Mehdi Moghani Bashi; Mohammad Hedayati (Ital Publication, 2019)
One of the most recent studies in the field of genetics is to investigate the role of microRNAs as biomarkers for the diagnosis of multiple sclerosis. It is an inflammatory and degenerative disease of the central nervous myelin, which is manifested in numerous small and large plaques in the white matter of the brain and spinal cord. Formerly called has-miR-377-3p, miR-377-3p is located within the chromosomal region 32q14, and is located in the SOD gene. SOD (Superoxide Dismutase) is a gene located on chromosomal region 22q21 and the protein encoded by this gene is the superoxide dismutase enzyme. The aim of this study was to evaluate the expression of miR-377 in people with RRMS (Relapsing-Remitting Multiple Sclerosis) and healthy individuals in the Isfahan population. The study included 49 patients with RRMS and 52 healthy individuals who had no history of autoimmune and inflammatory disease. Total RNA was extracted from the blood lymphocytes of the study subjects using Ficol and Trizol and then made using miRNA cDNA, cDNA specific kit, and expression was measured by real-time RT PCR in healthy subjects and patients. Was. According to the results, miR-377-3p expression was higher in patients than in healthy subjects (P = 0.036) and the sensitivity and diagnostic value of miRNA was AUC = 0.80 (Area under the Curve). ) is.  The results were consistent with previous studies and miR-377-3p could be used as a biomarker for the diagnosis of Multiple Sclerosis.